Ti6Al4V Thin Walls Production using Laser Directed Energy Deposition (L-DED) Process (International Journal of Engineering Materials and Manufacture, 2021)
One of the main applications of Directed Energy Deposition (DED) is the production of thin-wall structures, where it has significant advantages over traditional milling and machining techniques, or even welded analogues. These kinds of structures are frequently employed in aerospace components, field where titanium alloys have a primary role to play. Amongst them, the most employed is the Ti6Al4V with an alpha + beta alloy containing 6% Aluminium (Al) and 4% Vanadium (V). It has an excellent combination of strength and toughness along with excellent corrosion resistance. For the study hereby, thin-wall structures were constructed employing a Laser Directed Energy Deposition machine (L-DED), working with powder material. Analyse identified some microstructural and mechanical characteristics, thorough metallographic study, wear test (micro-adhesive) and micro hardness test. Finding a grain refined structure with competitive mechanical properties compared to materials manufactured by traditional processes. Results positioning DED as an attractive manufacturing technology, with a huge potential to improve costs and material usage, besides almost no restriction on component shape.